The Role of Probiotics in The Prevention of Colorectal Cancer - Muhammad Ridho Mandiri; Wendy P; Pariyana Pariyana (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Colorectal cancer (CRC) is the most common malignant tumor of the colon and rectum in the gastrointestinal tract which is one of the major health problems in the world with the fourth leading cause of death in the world. Various sources state that the incidence of CRC is caused by an imbalance of intestinal micro flora. It is important to maintain a balance of live microorganisms in sufficient quantities to provide health benefits called probiotics. Probiotics can maintain intestinal integrity, regulate bowel movements, increase lactose intolerance, thereby boosting immunity and helping prevent overgrowth of harmful bacteria and fungal infections. Through non-specific physiological mechanisms and immunological mechanisms, probiotics have roles such as initiating antiproliferative responses and apoptosis of CRC cells, supporting the function of the intestinal mucosal barrier by producing mucus, inhibiting the enzymatic activity of pathogenic bacteria such as β-glucuronidase, β-glucosidase, azoreductase, and nitroreductase so as to prevent colorectal cancer. In addition, it is necessary to make a diet and regulate a good diet in order to create homeostasis of microorganisms, normal intestinal flora.